Development and Application of a Duplex Droplet Digital Polymerase Chain Reaction Assay for Detection and Differentiation of EP402R-Deleted and Wild-Type African Swine Fever Virus - Zhu, Junhai; Jian, Weijun; Huang, Yifan; Gao, Qi; Gao, Fei; Chen, Huahan; Zhang, Guihong; Liao, Ming; Qi, Wenbao (Frontiers in Veterinary Science, 2022)
African swine fever (ASF) is a highly fatal porcine disease caused by the African swine fever virus (ASFV), and resulting in huge economic losses across the globe. ASF has been raging in China for three years and recently EP402R-deleted ASFV strains emerged, showing sub-acute or chronic symptoms in pigs and providing novel difficulties to monitor and control the disease as EP402R-deleted strains possess no hemadsorption ability. In addition, the gene deletion virus with low viral load is prone to results retest or false negative due to the high CT value under the current real-time PCR detection method. Thus, a new method is needed to detect and distinguish wild strains and gene-deleted viruses. In this study, a duplex droplet digital polymerase chain reaction (ddPCR) assay based on the ASFV B646L and EP402R genes was established and showed good linearity (R2＞0.99). The limit of detection for duplex ddPCR was 52 copies per reaction and 8.6 copies per reaction for B646L and EP402R. No cross-reaction with other porcine viruses (CSFV, PRRSV, PEDV, JEV, PPV and PCV2) was identified by this assay. In addition, 44 ASFV-suspecious clinical samples as well as EP402R-deleted ASFV were tested in parallel by duplex real-time PCR and ddPCR, indicative of a higher sensitivity which belonged to the duplex ddPCR assay. In summary, this is first time that duplex ddPCR assay has been successfully developed to provide an efficient method to detect and differentiate ASFV wild-type and gene-deleted strains.